The State of India’s Urban Poverty - Om Prakash Mathur (Asian Development Review, 1994)
Over the last two decades, the incidence of poverty has declined in India. Indeed, using the official data on poverty incidence without any form of adjustment, the decline would appear to be dramatic, with the headcount index dropping from 51.5 per cent in 1972/73 to 29.9 per cent in 1987/88, and the absolute numbers of the poor from 291.6 million to 237.67 million during the same period…